Global Attractivity for Lasota–Wazewska-Type System with Patch Structure and Multiple Time-Varying Delays - Zhiwen Long; Yanxiang Tan (Complexity)
This paper aims to study the asymptotic behavior of Lasota–Wazewska-type system with patch structure and multiple time-varying delays. Based on the fluctuation lemma and some differential inequality techniques, we prove that the positive equilibrium is a global attractor of the addressed system with small time delay. Finally, we provide an example to illustrate the feasibility of the theoretical results.